2008
DOI: 10.1021/ef800155v
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH of the Impregnation Solution on the Catalytic Properties of Co/γ-Alumina for Fischer−Tropsch Synthesis

Abstract: The Co/γ-Al2O3 catalysts were prepared by the slurry impregnation of an aqueous solution of cobalt(II) nitrate precursor. Nitric acid or ammonium hydroxide was added to the cobalt nitrate solution, during impregnation, to give an acidic or basic environment. The changes in the particle size of cobalt species were estimated by X-ray diffraction (XRD) and hydrogen chemisorption. The reduction degree of cobalt oxides was measured by temperature-programmed reduction (TPR). The catalysts prepared under acidic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 41 publications
(53 reference statements)
0
21
0
Order By: Relevance
“…Nowadays, elements other than noble metal, such as Zr [22], alkali earth elements [23], rare earth elements [24], and others [25][26][27], are examined as the reduction promoter. Other methods, such as improvement in the preparation method of Co/Al 2 O 3 catalysts [28][29][30][31][32][33] and structural control of Al 2 O 3 support [34][35][36][37][38][39], are also studied in order to improve the Co reducibility of Co/Al 2 O 3 catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, elements other than noble metal, such as Zr [22], alkali earth elements [23], rare earth elements [24], and others [25][26][27], are examined as the reduction promoter. Other methods, such as improvement in the preparation method of Co/Al 2 O 3 catalysts [28][29][30][31][32][33] and structural control of Al 2 O 3 support [34][35][36][37][38][39], are also studied in order to improve the Co reducibility of Co/Al 2 O 3 catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the catalytic performances of CoO x /c-Al 2 O 3 catalysts in these reactions are mainly related to the dispersion, valence and interaction of surface cobalt species with c-Al 2 O 3 , which are dependent on the preparation conditions including cobalt precursors, calcination temperature and atmosphere, etc. [16][17][18][19][20][21]. Among these factors, cobalt precursors could greatly influence the type and dispersion of cobalt species.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was observed that the reagent nature, operation conditions (pH…) and synthesis method used can influence the distribution and the active species nature [53]. A pH modification can alter the particle size [57]. The citric acid use in the case of the IMP method favors a "fully" dispersed active species [58].…”
Section: Biginelli Reactionmentioning
confidence: 99%